The Evaluation of serum fucose and fucose related parameters in beta- thalassemia major - Jalal, Heba Hasan; Muhialdin Ahmad, Bakhtiar (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Beta-thalassemia syndrome is characterized by either absent or lower-than-normal production of the beta-globin chain in hemoglobin, which can cause various health problems. α- L-fucose is a methyl pentose sugar, which is a part of the glycan’s of a significant category of compounds referred to as glycoconjugates; glycoproteins and glycolipids. The major aim of the current study is to evaluate using serum fucose parameters as biomarkers or indicators for beta- thalassemia disease. Methods: The current study was materialized on 45 Beta-thalassemia major patients and 45 healthy volunteer individuals. Blood sample collections were performed at Thalassemia Center (Akre and Erbil). Serum Fucose and related parameters total fucose (TF), protein bound fucose (PBF), protein bound hexose (PBH), lipid associated fucose (LAF), and free fucose (FF) were measured using UV/VIS spectrophotometry. Results: Beta-thalassemia major (BTM) patients had a significantly higher serum levels of TF and FF compared to the controls. A significant reduction in serum PBF was observed in patients. However, differences in PBH and LAF were not statistically significant. The PBH mean and standard deviation in patients were 6.421 and 3.085, respectively, compared to 6.817 and 3.758 in controls (P = 0.5858). For LAF, patient values were 3.281 and 2.225, versus 2.452 and 1.960 in controls (P = 0.0640). Conclusion: The results inferred significant increase in serum TF and FF, and a significant decrease in serum (PBF) in Beta-thalassemia major patients. The results suggest that TF, FF and PBF parameters can be used as diagnostic markers for the disease.